Building infrastructure and networks – rewards and challenges - Schwartz-Soicher, Ofira; Hayslett, Michele (IASSIST Quarterly, 2024)
Welcome to the third issue of IASSIST Quarterly for 2024, IQ 48(3). As we are moving towards an open research environment, institutions are building infructractures that will enable sharing data and other research resources with a wider audience. The authors of the three papers in this issue offer our readers the benefit of their experience by sharing what they have learned through the process of establishing new infrustractures and networks. The article ”Future models and architecture of data repositories in African universities,” describes the existing landscape of data repositories in African universities. Chigwada and Chiware use a review of existing literature to identify requirements for establishing an institutional data depository, and also identify successes and challenges. Based on their research they offer a roadmap for universities in Africa that are interested in establishing a data repository. The second article titled ”Working towards securing and building a trusted institutional research data repository through the CoreTrustSeal process: case of Cape Peninsula University of Technology data repository” seems like a natural extention of the previous one. The three authors, Lockhart, Xesi and Chiware (a co-authors of the previous paper), describe the process of establishing a research data repository at Cape Peninsula University of Technology. They provide details about the journey, starting with developing Open Access (OA) and Research Data Management (RDM) policies, identifying tools and developing the infrustructure needed for a an institutional data repository and data preservation, and developing a training program for faculty, students and staff. Additionally the authors comment on their experience, challenges and lessons learned from the application for CoreTrustSeal (CTS) certification for their newly created repository, eSango. In their article, ”Building human networks to drive forward innovations in international data access: Introducing the International Secure Data Facility Professionals Network (ISDFPN),” authors Wiltshire, Lichtwardt and Bishop describe the motivation and process of establishing the International Secure Data Facility Professional Network (ISDFPN), a forum that brings together international colleagues to share expertise and experience, and to collaborate in developing Trusted Research Environments (TREs). We hope you enjoy reading. Ofira Schwartz and Michele Hayslett, September 2024